The fairness of human resource management practices: an assessment by the justice sensitive - Haines, Victor Y.; Patient, David; Guerrero, Sylvie (Frontiers in Psychology, 2024)
Introduction Although fairness is a pervasive and ongoing concern in organizations, the fairness of human resource management practices is often overlooked. This study examines how individual differences in justice sensitivity influence the extent to which human resource management practices are perceived to convey principles of organizational justice. Methods Analysis was performed on a matching sample of 283 university students from three academic units in two countries having responded at two time points. Justice sensitivity was measured with the 40-item inventory developed and validated by Schmitt et al. (2010). Respondents were instructed to indicate to what extent each of 61 human resource management practices generally conveys principles of organizational justice. Results Justice sensitivity was positively associated with subsequent assessments of the justice contents of human resource management practices. The distinction between self-oriented and other-oriented justice sensitivities was helpful in determining perceptions of these human resource management practices and of a subset of pay-for-performance practices. Discussion The findings inform current research about the meanings borne by human resource management practices, and also increase understanding of entity judgment formation as an important aspect of systemic justice.